2008
DOI: 10.1128/cvi.00186-07
|View full text |Cite
|
Sign up to set email alerts
|

Double-Antigen Enzyme-Linked Immunosorbent Assay for Detection of Hepatitis E Virus-Specific Antibodies in Human or Swine Sera

Abstract: A new double-antigen sandwich-based enzyme-linked immunosorbent assay (ELISA) for the detection of total antibodies (immunoglobulin G [IgG] and IgM) specific for hepatitis E virus (HEV) was developed by utilizing well-characterized recombinant protein ET2.1 and its peroxidase-labeled counterpart. Our study showed that the ELISA detected all the positive patient samples (n ‫؍‬ 265) regardless of whether they contained IgM or IgG antibodies, or both, while it maintained an excellent specificity of 98.8% with sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…Due to failure in expression of the entire ORF2 in the E. coli expression system, carboxy-and amino-terminal segments of the CP were generated in E. coli. In line with previous investigations [40][41][42], the carboxy-terminal segments spanning aa residues 326-608 and 326-660 were found to be highly reactive with a pool of anti-HEV positive human sera. Additionally, immunodominant antigenic regions were previously found in this region using peptide-based assays [43,44].…”
Section: Discussionsupporting
confidence: 68%
“…Due to failure in expression of the entire ORF2 in the E. coli expression system, carboxy-and amino-terminal segments of the CP were generated in E. coli. In line with previous investigations [40][41][42], the carboxy-terminal segments spanning aa residues 326-608 and 326-660 were found to be highly reactive with a pool of anti-HEV positive human sera. Additionally, immunodominant antigenic regions were previously found in this region using peptide-based assays [43,44].…”
Section: Discussionsupporting
confidence: 68%
“…HEV IgM ELISA 3.0 and the Assure HEV IgM rapid test (MP Diagnostics) are based on a conformational ORF2-encoded epitope from a genotype 1 strain, the ORF2.1 antigen, considered highly conserved between HEV strains (1). Their good sensitivities observed in the present work are in keeping with a previous study that demonstrated that the ORF2.1 antigen is suitable for detecting total anti-HEV antibodies in swine infected with genotype 3 (5).…”
supporting
confidence: 78%
“…First, it incorporates antigens representing all four HEV genotypes, so allowing for the detection of antibodies generated in the host regardless of the genotype of the infecting HEV. Other DASAs developed for anti-HEV detection (14,22,55,63) mostly utilize antigenic preparations derived from one genotype only. Second, the highly immunodominant p166 antigens (37) are used to capture antibody, as well as to report its solid-phase capture, thereby conferring both sensitivity and specificity to anti-HEV detection.…”
Section: Discussionmentioning
confidence: 99%